DAMPAK KEBERADAAN WISATA PANTAI BAHARI BAGI PERUBAHAN SOSIAL MASAYRAKAT DI DESA JAWAI LAUT - Pratiwi, Indah; Rustiyarso, Rustiyarso; Hidayah, Riama Al (Universitas Tanjungpura, 2023)
This study aims to determine the impact of the existence of marine tourism for social change in the community in Jawai Laut Village, South Jawai District. The method used is descriptive qualitative. Data collection tools are in the form of interview guides, observation guides, documentation in the form of photographs and data archives that are needed. The data collection techniques used are observation, interviews and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The analysis in this study is presented descriptively by using 5 informants. The results of the study show that the impact of the existence of seashore tourism for social change in the Jawai community is that it is more towards a positive impact in the form of tourism development being well received by the people in Jawai Laut Village. The impacts that affect social change are positive and negative impacts. Positive changes in the form of increasing community participation and concern, opening up new business opportunities for the community, adding new knowledge to the community and increasing education and community skills. negative changes for the natural environment in the form of natural phenomena that exist around the coast in the form of a lot of garbage damaged roads and for the cultural environment which includes values, behavior, moral habits, community laws in the form of deviant behavior and habits influenced by people or visitors who come from from outside the area who provide examples of behavior that is not in accordance with the customs of the local community, but can be overcome by the community by making regulations and sanctions, mutual cooperation between the community and managers and visitors who come.